Islamic Approaches to Darwin's Theory of Evolution: Threats or Rationalization of the Doctrine of Human Origins? - Santi, Selvia; Nadeem Iqbal (Hikmatuna : Journal for Integrative Islamic Studies, 2021)
Darwin's theory of evolution continues to be a source of contention for academics concerned with the main issues of Islam and science in the twentieth century. As such, this research seeks to elicit perspectives from Islamic scholarly figures such as Seyyed Hossein Nasr, Zaghloul Al-Najjar, and Nidhal Guessoum. The three figures have varying perspectives on Darwin's theory of evolution. This divergent interpretation of Darwin's theory of evolution demonstrates that the debate on Islam and science did not totally result in the merger of the two, as all Muslim scholars agreed. This research employs Michel Foucault's archaeology and genealogy theories to examine the growth of Darwin's theory of evolution in the Islamic world, as symbolized by the three thinking figures. The findings indicated that Nasr expressly rejected Darwin's theory of evolution, which had been subjected to scientific and philosophical scrutiny. Al-Najjar says that the attitude of rejection and general acceptance of evolution theory is incorrect. By contrast, Guessoum views Darwin's theory of evolution as a factual truth that must be understood through the lens of Islam in order to generate theistic conceptions of evolution.